Knowledge management in globally distributed software development teams: Sensemaking challenges - Aman, Aini; Nicholson, Brian (2012)
Offshore software development presents a variety of knowledge management challenges. In this paper, we aim to improve our understanding of knowledge management challenges faced by globally distributed software development teams. Case study findings are analysed across two phases of initiation and growth. In the initiation phase we identify sense making challenges and the growth phase presents practices that were undertaken to cope with the challenges. The paper contributes the theoretical concept of imagination to the sensemaking literature as well as advancing our understanding of practices to overcome knowledge management challenges.